Vampires do hunt marshmallow bunnies - Jones, Marcia Thornton; Dadey, Debbie; Dreidemy, Joelle (New York : Scholastic, 2008)
All the candy is suddenly missing in Bailey City. What will happen to the Easter egg hunt without candy?